Cultural Diversity among the Employees and its Effect in Organizational Climate - Dr. G. Balamurugan; B. Santhiya (International Journal of Engineering and Management Research, 2020)
Cultural diversity is a group of diverse individuals from different cultures or societies. The study is conducted to explore how manage workforce diversity and its consequences to the company’s existence as well as examine how companies’ deal with challenges that comes with employees from diverse cultural backgrounds. The study describe diversity challenges that can affect the working climate and conflict between the employees through the diversity .The result shows that cultural diversity plays an effective role in some companies however inadequate mentoring and guidance could cause a company low productivity. For this reason there is must be regular improvement in ways to effectively manage a cultural diverse in workforce as the world keeps advancing.